Combat surgeons - Laffin, John (Sutton, 1999)
To the press, the politicians and the generals, the tens of thousands of wounded that result from a modern large-scale battle are thought of as "casulaties". To the dedicated surgeons, doctors and their staff they are individuals in need of expert help. Throughout history, Armed Services doctors have faced not only appalling medical difficulties: they have also had to fight apathy, ignorance and hidebound conservatism to win better conditions and treatment for the fighting man. Many have had the misfortune to serve during eras when soldiers and sailors were considered as expendable as the missiles they used. Here is the full story of military medicine - from ancient, magical remedies, boiling oil to cauterize amputations, bleeding and leeching, to anaesthetics, blood transfusions, plastic surgery and life-saving drugs, inoculations and vaccinations. The narrative ranges from the Middle Ages to the conflicts of Vietnam, the Falklands and the Gulf, and examines the role of the combat surgeon in the age of nuclear, biological and chemical warfare.